Long-circulation lithium-rich ruthenium-based positive electrode material based on high-energy ball milling morphology regulation and preparation method thereof
By introducing titanium and chromium into Li2RuO3 materials and using high-energy ball mill to regulate the morphology, lithium-rich ruthenium-based cathode material with improved electrochemical performance and cyclic stability was prepared, which solved the problem of poor long cycle stability of existing Li2RuO3 materials.
Patent Information
- Application Number
- CN202510038532.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
There are differences in the long cycle stability of existing Li2RuO3 materials, with low first discharge specific capacity and poor cycle stability.
By introducing titanium and chromium elements and using high-energy ball mill to regulate the morphology, lithium-rich ruthenium-based cathode material with chemical expression Li2Ru1-x-yTixCryO3 was prepared to improve its electrochemical performance and cyclic performance.
The cycle stability of the lithium-rich ruthenium-based cathode material was significantly improved, and the capacity retention rate of 300 cycles at 0.5C increased from 67.7% to 95.8% to 98.7%.
Smart Images

Figure CN119852384A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium-rich ruthenium-based positive electrode material and a preparation method thereof, and belongs to the field of preparation of lithium battery positive electrode materials. Background Art
[0002] For typical LiTMO2 series layered materials, if 1 / 3 of the metal elements in the transition metal layer are replaced with lithium ions, Li2MO3 series materials can be obtained. Therefore, another way to express the molecular formula of Li2TMO3 material is Li(Li 1 / 3TM 2 / 3 )O2. The lithium ions in the transition metal layer are surrounded by 6 transition metal ions, forming a honeycomb structure, which reduces the symmetry of the material and causes the Li2TMO3 structural materials to be monoclinic. According to the different transition metal types, there are also certain differences in the space group of Li2TMO3: C2 / c (M=Ru, Ti, Zr), C2 / m (M=Mn, Sn, Ir, Rh), etc. Li2RuO3, as a member of the Li2MO3 structural material, is a good electrode material for lithium ion embedding / ejection. Li2RuO3 is a layered structure composed of a lithium ion layer and a transition metal layer. The space group is C2 / c with monoclinic symmetry. Its experimental lattice parameter ( α=90°,β=100.073°,γ=90°) was reported by Kobayashi et al. The Li in the lithium layer occupies the 4e(0,y,1 / 4) position, and the transition metal layer consists of 1 / 3Li + and 2 / 3Ru 4+ Composition, Li and Ru occupy the positions of 4d (1 / 4, 1 / 4, 1 / 2) and 8f (x, y, z) respectively. + With 6 Ru 4+ Forming a honeycomb superlattice structure of LiRu6, the adjacent Ru 4+ The ions are linked by metallic bonds, but due to the dimerization of Ru, the Ru-Ru bond lengths are unequal. Both Li ions and Ru ions form octahedral structures with oxygen ions and occupy the center of the octahedron. Adjacent octahedra are connected to each other in a shared edge manner. These excess lithium ions in the Li2RuO3 positive electrode material can form a unique cation configuration, arranged in a honeycomb shape, which is called a "superlattice structure". It is this unique "superlattice structure" that gives the Li2RuO3 material a stable structure during the charge and discharge process. In order to explore its discharge capacity, the Thackeray research group adjusted the electrochemical voltage range of the Li2RuO3 material to 2.8-4.6V, and the initial charge capacity was increased to 310mAh g -1, which corresponds to 94% of lithium ions being released from the crystal structure, meaning that all lithium ions, including those in the transition metal layer, can participate in the electrochemical reaction. However, the initial discharge capacity is only 245 mAh g -1 , 15% of the lithium ions cannot be embedded into the layered structure again. Not only is the initial coulombic efficiency low, but after only 20 cycles, the reversible specific capacity is only 190 mAh g -1 , the cycle stability is poor. Summary of the invention
[0003] The present invention aims to solve the technical problem of poor long-cycle stability of existing Li2RuO3 materials, and provide a long-cycle lithium-rich ruthenium-based positive electrode material based on high-energy ball milling to control the morphology and a preparation method thereof. The method introduces two elements, titanium and chromium, to modify the lithium-rich ruthenium-based positive electrode material through high-energy ball milling to control the morphology, thereby improving its electrochemical performance and cycle performance.
[0004] The chemical expression of the long-cycle lithium-rich ruthenium-based positive electrode material based on high-energy ball milling to control the morphology of the present invention is Li2Ru 1-x-y Ti x Cr y O3, where x=y=0.0375~0.125.
[0005] The above-mentioned method for preparing a long-cycle lithium-rich ruthenium-based positive electrode material with morphology controlled by high-energy ball milling is carried out according to the following steps:
[0006] 1. According to the mass ratio of Li2CO3, RuO2, TiO2 and Cr2O3 powders being 1:(1.23-1.67):(0.04-0.14):(0.04-0.13), weigh Li2CO3, RuO2, TiO2 and Cr2O3 powders, mix them and add them into a high-energy ball mill, and ball mill them at a rotation speed of 280-320 rpm for 2.8-3.2 hours to obtain a mixed powder;
[0007] 2. Place the mixed powder in a high-temperature furnace and calcine it at 950-1050°C in an oxygen environment for 14-16 hours to obtain a long-cycle lithium-rich ruthenium-based positive electrode material with morphology controlled by high-energy ball milling.
[0008] Furthermore, in step 1, the mass ratio of Li2CO3, RuO2, TiO2 and Cr2O3 powder is 1:(1.35-1.51):(0.04-0.14):(0.04-0.13). Li will be lost during the calcination process, so excess Li2CO3 is added to compensate for the Li lost during the calcination process.
[0009] Furthermore, the calcination temperature in step 2 is 1000° C. and the calcination time is 15 hours.
[0010] Compared with the existing lithium-rich ruthenium-based Li2RuO3, the long-cycle lithium-rich ruthenium-based positive electrode material based on high-energy ball milling to control the morphology of the present invention is to introduce Ti and Cr into the traditional lithium-rich ruthenium-based Li2RuO3. By selecting titanium elements with stronger metal oxygen bonding ability, it is beneficial to stabilize the crystal structure and improve the stability of the material. The metal chromium with a radius similar to that of the metal ruthenium atom is selected for titanium and chromium to work together, while increasing the capacity, avoiding major changes in the crystal structure, and improving the capacity and long-cycle stability of the positive electrode material. The capacity retention rate of the lithium-rich ruthenium-based positive electrode material of the present invention is increased from 67.7% to 95.8% to 98.7% after 300 cycles at 0.5C.
[0011] The preparation method of the lithium-rich ruthenium-based positive electrode material of the present invention firstly controls the rotation speed and time of high-energy ball milling to achieve the purpose of sample crushing, mixing and alloying under appropriate grinding efficiency and grinding intensity, thereby obtaining LRTCO (Li2Ru 1-x-y Ti x Cr y O3), and then adjust the high temperature calcination conditions in an oxygen environment to obtain the best performance lithium-rich ruthenium-based positive electrode material. The method is simple and can be used in the field of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Li2RuO3 prepared in Comparative Example 1 and Li2Ru prepared in Example 1 0.925 Ti 0.0375 Cr 0.0375 XRD spectrum of O3;
[0013] Figure 2 is a SEM image of Li2RuO3 prepared in Comparative Example 1;
[0014] Figure 3 Li2Ru prepared in Example 1 0.925 Ti 0.0375 Cr 0.0375 SEM image of O3;
[0015] Figure 4 Li2Ru prepared in Example 1 0.925 Ti 0.0375 Cr 0.0375 O3 and the cycle performance curve of Li2RuO3 prepared in comparative example 1. DETAILED DESCRIPTION
[0016] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the invention shall be included in the protection scope of the present invention. The preparation method of the novel lithium-rich ruthenium-based positive electrode material of the present invention is described in detail below through specific embodiments.
[0017] Example 1: The preparation method of the long-cycle lithium-rich ruthenium-based positive electrode material based on high-energy ball milling to control the morphology of this embodiment is carried out according to the following steps:
[0018] 1. Weigh 0.005232 mol (0.3866 g) of Li2CO3, 0.004400 mol (0.5856 g) of RuO2, 0.0001784 mol (0.01425 g) of TiO2 and 0.00008922 mol (0.01356 g) of Cr2O3 powder, mix them and add them into a high-energy ball mill. The ball milling beads are made of agate balls, and the ball-to-material mass ratio is 20:1. Ball milling is carried out at a speed of 300 rpm for 3 hours to obtain a mixed powder.
[0019] Second, the mixed powder was placed in a high-temperature furnace and calcined at 1000°C in an oxygen environment for 15 hours to obtain a long-cycle lithium-rich ruthenium-based cathode material with morphology controlled by high-energy ball milling, which is expressed as Li2Ru 0.925 Ti 0.0375 Cr 0.0375 O3.
[0020] Comparative Example 1: This comparative example is to prepare a lithium-rich ruthenium-based positive electrode material Li2RuO3 positive electrode material, and the specific preparation method is as follows:
[0021] 1. Weigh 0.005143 mol (0.38 g) of Li2CO3 powder and 0.004658 mol (0.62 g) of RuO2 powder, mix them and add them into a high-energy ball mill. The ball milling beads are made of agate balls with a ball-to-material mass ratio of 20:1. Ball milling is carried out for 3 hours at a speed of 300 rpm to obtain a mixed powder.
[0022] 2. The mixed powder is placed in a high-temperature furnace and calcined for 15 hours at a temperature of 1000°C in air to obtain a lithium-rich ruthenium-based positive electrode material, the expression of which is Li2RuO3.
[0023] Li2RuO3 prepared in Comparative Example 1 and Li2Ru prepared in Example 1 0.925 Ti 0.0375 Cr 0.0375 O3 was tested by XRD, and the obtained XRD spectrum was as follows Figure 1 As shown, from Figure 1It can be seen that the prepared samples have good crystallinity and layered structure, and according to the main peak offset direction, it can be seen that the long-cycle lithium-rich ruthenium-based positive electrode material based on high-energy ball milling to control the morphology has a smaller interplanar spacing, indicating that the role of the metal valence bonds Ti-O and Ru-O in the lithium-rich ruthenium-based positive electrode material is further enhanced. 0.925 Ti 0.0375 Cr 0.0375 O3 was subjected to SEM test, and the SEM photo of Li2RuO3 prepared in Comparative Example 1 is shown in Figure 2 As shown, Li2Ru prepared in Example 1 0.925 Ti 0.0375 Cr 0.0375 The scanning electron microscope photo of O3 is shown in Figure 3 As shown, from Figure 2 , 3 It can be seen that the primary particle size of the sample of Example 1 is smaller than that of the sample of Comparative Example 1, the shape is more regular, the surface is smoother, and the particle size distribution is more uniform. The regular shape makes the diffusion length equal, which is conducive to achieving uniform lithium ion insertion and extraction; the smooth surface is conducive to further reducing the side reaction with the electrolyte, and the smaller particle size is conducive to the infiltration of the electrolyte and Li + diffusion, and a proper reduction in the primary particle size will reduce the Li + The diffusion path gives the material better discharge capacity and rate performance.
[0024] The long-cycle lithium-rich ruthenium-based positive electrode material with morphology controlled by high-energy ball milling obtained in Example 1 and the lithium-rich ruthenium-based positive electrode material prepared in Comparative Example 1 were used as electrode active materials for electrochemical testing. The assembly steps of the battery are as follows: the electrode active material, the conductive agent Super P, and polyvinylidene fluoride (PVDF) are weighed at a mass ratio of 8:1:1, mixed in a mortar and transferred to a weighing bottle. Subsequently, an appropriate amount of N-methylpyrrolidone (NMP) is added to the weighing bottle. After the solid-liquid mixture in the bottle becomes viscous, a magnet is added and magnetically stirred at room temperature for 6 hours to obtain a viscous but fluid electrode paste. Use a scraper to scrape the electrode paste on the electrode sheet, and the active material loading of the obtained electrode sheet is 2-3 mg cm -2 When assembling the CR2025 button half-cell, the entire process is carried out in a glove box protected by high-purity argon, and the water and oxygen content are controlled below 0.1ppm. The order of assembly is positive electrode shell → positive electrode → diaphragm → electrolyte → negative electrode → negative electrode shell. The positive electrode is a prepared circular electrode sheet, the negative electrode is a metal lithium sheet, the diaphragm is celgrad 2500, and the electrolyte is 1.0mol L -1The organic solution of LiPF6, the electrolyte solvent is a mixture of ethyl carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1. After the button battery is sealed with a sealing machine, it is left to stand for 6 hours before testing. The constant current charge and discharge test is carried out on the Xinwei battery tester, the test temperature is 25℃, and the voltage range of the charge and discharge test is 2.5~3.9V. The cycle performance curve under 0.5C condition is as follows Figure 4 As shown, from Figure 4 It can be seen that Li2Ru prepared in Example 1 0.925 Ti 0.0375 Cr 0.0375 The capacity retention rate of O3 is higher than that of Li2RuO3 in comparative example 1, and the capacity retention rate reaches 98.7% after 300 cycles at 0.5C. The capacity retention rate of Li2RuO3 prepared in comparative example 1 after 300 cycles at 0.5C is only 67.9%.
[0025] Example 2: The preparation method of the long-cycle lithium-rich ruthenium-based positive electrode material based on high-energy ball milling to control the morphology of this example is carried out according to the following steps:
[0026] 1. Weigh 0.005267mol (0.3892g) Li2CO3, 0.004309mol (0.5735g) RuO2, 0.0002394mol (0.01912g) TiO2 and 0.0001197mol (0.01819g) Cr2O3 powder, mix them and add them into a high-energy ball mill. The ball milling beads are made of agate balls, and the ball-to-material mass ratio is 20:1. Ball milling is carried out at a speed of 300rpm for 3 hours to obtain a mixed powder;
[0027] Second, the mixed powder was placed in a high-temperature furnace and calcined at 1000°C in air for 15 hours to obtain a long-cycle lithium-rich ruthenium-based cathode material with morphology controlled by high-energy ball milling, which is expressed as Li2Ru 0.900 Ti 0.050 Cr 0.050 O3.
[0028] The Li2Ru prepared in Example 2 was treated in the same manner as in Example 1. 0.900 Ti 0.050 Cr 0.050 The electrical properties of O3 were tested, and the results showed that the capacity retention rate reached 98.4% after 300 cycles at 0.5C.
[0029] Example 3: The preparation method of the long-cycle lithium-rich ruthenium-based positive electrode material based on high-energy ball milling to control the morphology of this embodiment is carried out according to the following steps:
[0030] 1. Weigh 0.005338 mol (0.3944 g) of Li2CO3 powder, 0.004124 mol (0.5489 g) of RuO2 powder, 0.0003638 mol (0.02906 g) of TiO2 powder and 0.0001819 mol (0.02765 g) of Cr2O3 powder, mix them and add them into a high-energy ball mill. The ball milling beads are made of agate balls, and the ball-to-material mass ratio is 20:1. Ball milling is carried out at a speed of 300 rpm for 3 hours to obtain a mixed powder.
[0031] Second, the mixed powder was placed in a high-temperature furnace and calcined at 1000°C in air for 15 hours to obtain a long-cycle lithium-rich ruthenium-based cathode material with morphology controlled by high-energy ball milling, which is expressed as Li2Ru 0.850 Ti 0.075 Cr 0.075 O3.
[0032] The Li2Ru prepared in Example 3 was treated in the same manner as in Example 1. 0.850 Ti 0.075 Cr 0.075 The electrical properties of O3 were tested, and the results showed that the capacity retention rate reached 97.2% after 300 cycles at 0.5C.
[0033] Example 4: The preparation method of the long-cycle lithium-rich ruthenium-based positive electrode material based on high-energy ball milling to control the morphology of this embodiment is carried out according to the following steps:
[0034] 1. Weigh 0.005484mol (0.4052g) of Li2CO3 powder, 0.003739mol (0.4977g) of RuO2 powder, 0.0005928mol (0.04735g) of TiO2 powder and 0.0003275mol (0.04977g) of Cr2O3 powder, mix them and add them into a high-energy ball mill. The ball milling beads are made of agate balls, and the ball-to-material mass ratio is 20:1. Ball milling is carried out at a speed of 300rpm for 3 hours to obtain a mixed powder.
[0035] Second, the mixed powder was placed in a high-temperature furnace and calcined at 1000°C in air for 15 hours to obtain a long-cycle lithium-rich ruthenium-based cathode material with morphology controlled by high-energy ball milling, which is expressed as Li2Ru 0.750 Ti 0.125 Cr 0.125 O3.
[0036] The Li2Ru prepared in Example 4 was treated in the same manner as in Example 1. 0.750 Ti 0.125 Cr 0.125The electrical properties of O3 were tested, and the results showed that the capacity retention rate reached 95.8% after 300 cycles at 0.5C.
[0037] Comparative Example 2: This embodiment is different from Example 1 in that the ball milling in step 1 has a ball milling speed of 200 rpm and a ball milling time of 2 hours, and the other steps and parameters are the same as those in Example 1.
[0038] Comparative Example 3: This embodiment is different from Example 1 in that the ball milling in step 1 has a ball milling speed of 400 rpm and a ball milling time of 4 hours, and the other steps and parameters are the same as those in Example 1.
[0039] The Li2Ru prepared in Comparative Examples 2 and 3 was prepared by the same method as in Example 1. 0.925 Ti 0.0375 Cr 0.0375 The electrical properties of O3 were tested. The results showed that the Li2Ru prepared in Comparative Example 2 had a good electrical conductivity and good electrical conductivity at 0.5C for 300 cycles. 0.925 Ti 0.0375 Cr 0.0375 The O3 capacity retention rate is only 75.1%. 0.925 Ti 0.0375 Cr 0.0375 The O3 capacity retention rate is only 81.6%, which is lower than the capacity retention rate of the material prepared under the conditions of Example 1, indicating that too low or too high ball milling speed is not conducive to improving the material performance.
[0040] The above examples can prove that chromium improves the discharge capacity of the material, and titanium 1-x-y Ti x Cr y O3 can form a stronger Ti-O bond, which is beneficial to stabilize the crystal structure of Li2RuO3, improve its electrochemical performance, and help prevent huge changes in the crystal structure, and further increase its discharge specific capacity and capacity retention rate. Through the ball milling and calcination conditions selected by the present invention and the reasonable introduction of titanium and chromium, samples with greatly improved long-cycle performance can be prepared, and the discharge specific capacity, capacity retention rate and lithium ion diffusion rate of the samples can be improved; the preparation method is simple to operate, low in cost, and can be mass-produced.
Claims
1. A long-cycle lithium-rich ruthenium-based cathode material with morphology controlled by high-energy ball milling, characterized in that The chemical formula of this material is Li2Ru 1-x-y Ti x Cr y O3, where x=y=0.0375~0.
125.
2. A method for preparing a long-cycle lithium-rich ruthenium-based positive electrode material with morphology controlled by high-energy ball milling according to claim 1, characterized in that: The method proceeds as follows:
1. According to the mass ratio of Li2CO3, RuO2, TiO2 and Cr2O3 powders being 1:(1.23-1.67):(0.04-0.14):(0.04-0.13), weigh Li2CO3, RuO2, TiO2 and Cr2O3 powders, mix them and add them into a high-energy ball mill, and ball mill them at a rotation speed of 280-320 rpm for 2.8-3.2 hours to obtain a mixed powder; 2. Place the mixed powder in a high-temperature furnace and calcine it at 950-1050°C in an oxygen environment for 14-16 hours to obtain a long-cycle lithium-rich ruthenium-based positive electrode material with morphology controlled by high-energy ball milling.
3. The method for preparing the novel lithium-rich ruthenium-based positive electrode material according to claim 2, characterized in that: In step 1, the mass ratio of Li2CO3, RuO2, TiO2 and Cr2O3 powders is 1:(1.35~1.51):(0.04~0.14):(0.04~0.13).
4. The method for preparing the novel lithium-rich ruthenium-based positive electrode material according to claim 2 or 3, characterized in that: The calcination temperature in step 2 is 1000° C. and the calcination time is 15 hours.
Citation Information
Patent Citations
Lithium supplement material and preparation method thereof, positive pole piece and secondary battery
CN116230899A
Lithium supplement material and preparation method thereof, positive electrode material and secondary battery
CN118367149A
Lithium-rich nickel-manganese-cobalt cathode powders for lithium-ion batteries
WO2017051338A1
Layered sodium-ion battery positive electrode material, preparation method therefor, and use thereof
WO2024093126A1